Shaping Policy through Evidence : the Past, Present and Future - Weersinghe, M.C. (Faculty of Medicine, University of Colombo, 2020)
Public policies play a key role in the efforts to protect and improve population health. Over the past centuries, public health policies ...
Keywords: Public Health Policies; Population Health